Analisis Migrasi ke Kota Banda Aceh - Ikhsan Ikhsan; Muhammad Wali (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2014)
The aim of this study is to know the factors that influence the decision of migration to the city of Banda Aceh. This research was conducted in Banda Aceh and used purposive sampling to collect cross section data. Based on Slovin formula, the appropriate samples for this research are 60 respondents. The data were analyzed by using descriptive statistics. The results of this study showed that the people migrate to the city of Banda Aceh was influenced by age, education, income, marital status and ownership of the land in area where they came from. The main reason to migrate was to obtain a better job. The push factor that cause people to migrate was largely due to the low income in the area of origin. Therefore, the provincial government needs to accelerate development in all districts and cities in order to reduce inequality among regions.